Seasonal Predictability over Europe Arising from El Niño and Stratospheric Variability in the MPI-ESM Seasonal Prediction System - Domeisen, Daniela; id_orcid:0 000-0002-1463-929X; Butler, Amy H.; Fröhlich, Kristina; Bittner, Matthias; Müller, Wolfgang A.; Baehr, Johanna (Journal of Climate, 2015)
ISSN:0894-8755 ISSN:1520-0442